Analysis of the Effect of E-Services Quality on Customer Satisfaction and Repurchase Decisions on E-Commerce Shopee - Dalili Batrisyia; Minto Waluyo (Inovbiz: Jurnal Inovasi Bisnis, 2022)
Currently the times and technological developments are increasingly rapid and sophisticated so that people use digital technology more to meet their needs. This study aims to determine the effect and simultaneous equations of e-service quality variables (efficiency, fulfillment, reliability, privacy, responsiveness, compensation and contact) on satisfaction and repurchase decisions of Shopee e-commerce customers. This research was conducted using a quantitative descriptive approach. This study uses more than one endogenous variable, so the tools that can be used are SEM (Structural Equation Modeling) and PLS (Partial Least Square). However, in this problem the feasibility and compliance using SEM with the assumption of ML (Maximum Like-lihood) technique with a range of 100-200 samples. The results of the research on the analysis of the influence of e-service quality on customer satisfaction and repurchase decisions at E-Commerce Shopee that have been analyzed, obtained several conclusions, namely efficiency, fulfillment, reliability, responsiveness, privacy, compensation and contact variables have a significant effect if they become one variable. exogenous namely e-service quality. The e-service quality variable has a significant effect on customer satisfaction and repurchase decisions. Simultaneous equations obtained from the analysis of the effect of E-Service Quality on Customer Satisfaction and Repurchase Decisions at E-Commerce Shopee are Y1 = 0.835 X + Z2 and Y2 = 0.750 Y1 + Z3.